Vitamin D and Calcium Supplementation Reverses Tenofovir-Caused Bone Mineral Density Loss in People Taking ART or PrEP: A Systematic Review and Meta-Analysis - Bi, Xiaoyan; Liu, Fan; Zhang, Xiangjun; Wang, Hongyi; Ye, Zehao; Yun, Ke; Huang, Xiaojie; Ding, Haibo; Geng, Wenqing; Xu, Junjie (Frontiers in Nutrition, 2022)
Background The decrease of bone mineral density (BMD) after the intake of Tenofovir disoproxil fumarate (TDF)-based drugs in people living with HIV/AIDS (PLWHA) and HIV-negative key populations under pre-exposure prophylaxis (PrEP) regimen raised concerns. Previous findings on the effects of vitamin D (VD) and calcium supplements and the recovery of BMD loss were inconclusive. The optimal doses of VD and calcium and its supplementary duration remained unknown. Therefore, we conducted a systematic review and meta-analysis to synthesize current evidence on VD and calcium supplements to inform clinical practice. Methods We searched PubMed, Web of Science, Cochrane library, and EMBASE databases for all placebo-controlled trials and prospective cohort studies published before March 5, 2021 that investigated VD and calcium supplements in participants taking TDF-based drugs. The keywords calcium, vitamin D, Tenofovir, and BMD were used for the searches. The primary outcome was changes of spine and hip BMD. Subgroup analysis was performed to determine factors that were related to the effects of VD supplements on BMD. Locally weighted regression (loess) was used to determine the relationships of VD supplements, supplementary duration, and the change of BMD. This study was registered at PROSPERO (NO.42021231000). Findings Seven eligible studies including 703 participants were included in the analyses. The meta-analysis found that VD and calcium supplementation was related to a significant increase of BMD in the spine and hip [standardized mean difference (SMD) 0.43; 95% CI, 0.25 to 0.61, P=0.009]. Moreover, positive dose-response relationships were demonstrated between doses of VD and calcium supplements, supplementary duration, and BMD recovery. Patients who took VD with the dose level of 4000 IU/D obtained the highest BMD improvement (SMD 0.59, 95% CI, 0.43 to 0.74). No side effects were reported on VD and calcium supplementation. Interpretation We found VD and calcium supplementation was associated with increases of BMD in participants taking TDF-based drugs. An optimal supplementary dose of 4000IU/D for vitamin D was suggested. The findings could be used in clinical practice to improve BMD outcomes in people who take TDF-based drug.